The role of psychosocial safety climate in reducing workplace violence and enhancing coping among healthcare workers: A narrative review - Ely Zarina Samsudin; Mohd Hazim Ahmad Fuad; Nik Nairan Abdullah; Ahmad Nazim Aimran (Journal of Clinical and Health Sciences, 2026)
Introduction: Workplace violence (WPV) is a prevalent issue in healthcare, negatively impacting healthcare workers’ (HCWs) mental health and quality of patient care. Psychosocial safety climate (PSC) is an organisational construct prioritising psychological well-being and is increasingly recognised for its role in occupational safety and health. However, its influence on WPV and HCWs’ coping mechanisms remains underexplored. This review integrates existing literature to examine PSC and its relationships with WPV and HCWs’ coping mechanisms. Method: A narrative review was conducted using PubMed and Scopus to identify primary studies from 2010 to 2024 that examined PSC, WPV, and coping mechanisms among HCWs. Fifteen studies were analysed using relevant work stress models, including the Extended Job Demands-Resources model and the Transactional Model of Stress and Coping. Results: Globally, 62% HCWs reported experiencing WPV. While PSC enhances HCWs’ well-being through improved support and safety, many healthcare settings report low PSC levels. Emerging evidence suggests that PSC inversely correlates with WPV by fostering better workplace policies and communication. Additionally, PSC appears to moderate workplace deviant behaviours by encouraging adaptive coping, including problem-focused and emotion-focused strategies. However, direct empirical research linking PSC with WPV and HCWs’ coping remains limited. Conclusions: PSC is a critical yet under-researched factor in WPV prevention. As a modifiable organisational construct, future research should employ longitudinal and mixed-method designs to explore its role in reducing WPV and enhancing coping mechanisms. Findings may inform PSC-driven interventions to promote HCWs’ resilience, workplace safety, and WPV prevention.